Transient dissociation of bone metabolism induced by high performance exercise: a study in elite marathon runners - Crespo, R.; Revilla, M.; Villa, L. F.; Usabiaga, J.; Leibar, X.; Rico, H. (Calcified Tissue International, 1999)
Bone metabolism parameters were studied in 18 elite marathon runners (11 men and 7 women) who participated in the Marathon World Cup held at San Sebastian, Spain in 1993. Measurements were made before the race, immediately after the race, and 24 hours after the race. The most interesting finding was increased alkaline phosphatase (P < 0. 0001) and decreased tartrate-resistant acid phosphatase (P = 0.0035), which suggests that exercise produced uncoupling of the bone cell metabolism. Serum calcium corrected for proteins did not increase with exercise and at the end of the race there was a negative correlation between cortisol, which was significantly higher (P < 0. 0001), and corrected serum calcium (r = 0.53, P = 0.026) that was not present at baseline. Running time showed a significant negative correlation with baseline serum cortisol (r = -0.67, P = 0.0015) and a significant positive correlation with body mass index (r = 0.53, P = 0.0207). The increase in alkaline phosphatase persisted 24 hours after the race, which suggests that exercise produced an intense and sustained effect on osteogenic capacity.